Livelihoods, power, and food insecurity: adaptation of social capital portfolios in protracted crises—case study Burundi. Issue 2 (27th December 2012) - Vervisch, Thomas G.A.; Vlassenroot, Koen; Braeckman, Johan
<x xml:space="preserve">Abstract</x> The failure of food security and livelihood interventions to adapt to conflict settings remains a key challenge in humanitarian responses to protracted crises. This paper proposes a social capital analysis to address this policy gap, adding a political economy dimension on food security and conflict to the actor‐based livelihood framework. A case study of three hillsides in north Burundi provides an ethnographic basis for this hypothesis. While relying on a theoretical framework in which different combinations of social capital (bonding, bridging, and linking) account for a diverse range of outcomes, the findings offer empirical insights into how social capital portfolios adapt to a protracted crisis. It is argued that these social capital adaptations have the effect of changing livelihood policies, institutions, and processes (PIPs), and clarify the impact of the distribution of power and powerlessness on food security issues. In addition, they represent a solid way of integrating political economy concerns into the livelihood framework.